The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1111/j.1600-0404.1979.tb02951.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma HDL cholesterol in epileptics with elevated triglyceride and cholesterol

Abstract: Due to the metabolic changes induced, e.g. in the liver by anti-epileptic drugs, the significance of high serum triglyceride and cholesterol in epileptics was studied and the plasma HDL cholesterol level was compared in 190 epileptic patients with elevated or normal triglyceride and cholesterol, with the corresponding values in 43 healthy subjects. One-third of the epileptic patients showed elevated plasma HDL cholesterol levels. Female epileptics had higher plasma HDL cholesterol than the normolipidemic healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 13 publications
(8 reference statements)
2
1
0
Order By: Relevance
“…The results in our study findings are similar to those other investigations done by P Kumar et al, Pelkonen et al, Nikkila et al, and Luoma et al, also reported same findings i.e. an increase in TG, LDL-C and HDL-C levels in epileptic patients on long-term treatment with Phenytoin [5][6][7][8].…”
Section: Discussionsupporting
confidence: 92%
“…The results in our study findings are similar to those other investigations done by P Kumar et al, Pelkonen et al, Nikkila et al, and Luoma et al, also reported same findings i.e. an increase in TG, LDL-C and HDL-C levels in epileptic patients on long-term treatment with Phenytoin [5][6][7][8].…”
Section: Discussionsupporting
confidence: 92%
“…Hence, previous studies have shown that patients with epilepsy had increased carotid artery intimamedia thickness and increased vascular risk factors (Tan et al, 2009). This coincides with (Luoma et al, 1979) who reported that epileptic patients showed elevated plasma HDL cholesterol levels.…”
Section: Discussionsupporting
confidence: 77%
“…Clinical studies demonstrated a link between the use of CAR-activating drugs and the occurrence of metabolic disruptions in patients. Long-term use of phenobarbital (PB), a CAR activator, as an antiepileptic drug, induced a change in plasma lipid profiles of patients (3)(4)(5) and chronic treatment with other CAR activators like valproic acid or tamoxifen were associated with the occurrence of hepatic disorders (6,7).…”
Section: Introductionmentioning
confidence: 99%